Evaluation of Inhibitory Effect of Recreational Drugs on Dopaminergic Terminal Neuron by PET and Whole-Body Autoradiography. (29th April 2014) - Yeh, Skye Hsin-Hsien; Lin, Ming-Hsien; Kong, Fan-Lin; Chang, Chi-Wei; Hwang, Li-Chung; Lin, Chien-Feng; Hwang, Jeng-Jong; Liu, Ren-Shyan
Abstract : There is little investigation for the functional roles of peripheral dopamine. [ 18 F]FDOPA has been used in cancer imaging (i.e., neuroendocrine and tumors pancreatic tumors) and neuroimaging (i.e., Parkinson's disease and Huntington's disease). Here, we accessed side effects of recreational drugs such as ketamine, cocaine, and methamphetamine on dopamine neurons in peripheral organs by using positron emission tomography (PET) imaging and quantitative whole-body autoradiography (QWBAR) with [ 18 F]FDOPA. The images were applied for the measurement of specific binding ratios (SBRs) of striatum with the cerebellum as the reference region. Clear striatal [ 18 F]FDOPA-derived radioactivity was observed. Moderate level of radiotracer accumulation was presented in the mucosal layers of the stomach and small intestine. The medulla layers of kidney had higher radioactivity than that of the cortex. Blocking images markedly eliminated the specific binding of [ 18 F]FDOPA in the striatum and in peripheral organs such as stomachs, intestines, and kidney. Ketamine showed the highest inhibitory effect on striatal [ 18 F]FDOPA-derived radioactivity followed by cocaine and methamphetamine. The current results demonstrated a useful crossing-validating tool that enhances the capability of [ 18 F]FDOPA for further investigations of the alteration of dopaminergic neurons in the brain disorder or cancer diseases in peripheral tissues.